Does social risk management matter? influencing factors and their link to firms' financial performances / Tamoi Janggu ... [et al.] - Janggu, Tamoi; Sawani, Yussri; Yusoff, Haslinda; Darus, Faizah; Mohamed Zain, Mustaffa (Accounting Research Institute (ARI), 2017)
This article deals with the growing pressures and demands for emerging risk reporting that may help interested users assess the importance of social risk management for sustainable development. The objectives of this study were to examine the influence of individual and institutional ownership and stakeholders on social risk disclosures and the joint effects on firms’ financial performances. A content analysis on the 2013 and 2014 annual reports of all plantation companies was carried out and analyzed using partial least square (SEM_PLS) software version 3.2. Based on the tests, we found significant relationships between institutional ownership and the number of stakeholders with social risk disclosures. However, there were no significant relationships between individual ownership and social risk disclosures. In addition, we found significant relationships between social risks and firms’ financial performances. These findings revealed that institutional shareholders and the number of stakeholders had a significant influence in deciding the disclosure of social risk information. Interestingly to note that social risk information was found to be statistically significant on firms’ financial performance as measured by the firms’ net profits. This paper, therefore, endorsed the growing demand to fully embed social risk management in companies’ operations by both institutional shareholders and stakeholders in general.